Прокатний стан – джерело пізнання вібродинамічних процесів - Вереньов, В.В. (Physico-technological Institute of Metals and Alloys, 2023)
Using the example of the wide strip mill 1680 of the Zaporizhstal metallurgical plant, it is shown that field measurements allow one to obtain very valuable and useful information about the vibrodynamic processes in the equipment. As the main parameters of the mill, the moment of elastic forces on the shaft between the engine and the gearbox and the vibration at different points of the gear stand and gearbox housing were measured. The features of transients during the capture of the strip by rolls and during the interaction of the stands of the rough group through a thick rolling strip are established. The relationship of wear and gaps in the drive line with the time delay of the vibration sensors reaction to the shock load when capturing the strip is shown. The correlation dependence of the maximum dynamic moment when the strip is captured on the moment in the steady rolling mode is revealed, which allows monitoring loads taking into account the technical condition of the drive line. The value of joint measurements of the moment and vibration for the establishment of interconnections of elastic systems in transition modes, in particular, when rolling slabs with a curly leading edge, is shown. The importance of full-scale measurements in existing rolling mills consists not only in establishing the actual picture of oscillatory processes and the load level, but also in developing mathematical and computer models for filling a continuous group of stands with a strip, statistical modeling, and searching for new ways to test equipment. Large arrays of measurements always contain hidden patterns that have novelty and substantial informational content. Examples of scientific conclusions based on the measurements are given.